PENGARUH FASILITAS RUANG TUNGGU TERHADAP KEPUASAN PENUMPANG DI BANDAR UDARA DEPATI AMIR PANGKALPINANG - Elta Afitasari; Yulia Aji Puspitasari (LPPM Politeknik Pratama, 2023)
Facilities are important in the service business, where good enough facilities can make passengers feel satisfied and comfortable while in that place. Similarly, the waiting room facilities at the airport are used by passengers to wait before entering the plane. The waiting room provided must feel comfortable and safe, to provide the best performance to airport service users. This study aims to determine the effect of waiting room facilities on passenger satisfaction and to find out how much influence waiting room facilities have on passenger satisfaction at Depati Amir Pangkal Pinang Airport. This research was conducted at Depati Amir Airport Pangkal Pinang, this type of research used quantitative methods. Data sources in this study used primary and secondary data. While the data collection technique in this study used questionnaires distributed to passengers using Likert scale. The sample used in this study used 100 respondents. The data were tested using instrument tests, simple linear regression and hypothesis tests in the form of T tests and determination coefficient tests.